Determining the Electronic Structure and Thermoelectric Properties of MoS2/MoSe2 Type‐I Heterojunction by DFT and the Landauer Approach (Adv. Mater. Interfaces 11/2023). Issue 11 (14th April 2023) - López‐Galán, Oscar A.; Perez, Israel; Nogan, John; Ramos, Manuel
Abstract : Van der Waals Heterojunctions In article 2202339, Oscar A. López‐Galán and colleagues report a comprehensive study on MoS2 /MoSe2 Van der Waals heterojunction. The report suggests that properties of Van der Waals heterojunctions are highly dependent on the equilibrium conditions and their electronic and thermoelectric properties can be tuned accordingly. Furthermore, it suggests that the heterojunction can achieve ballistic transport under an applied biased with potential applications in nano transistors and solar cells.